Methodologies and indicators of academic, economic, social and technological impact of university scientific research - Díaz Corrales, A.V.; Sánchez Alonso, R. E.; Rosales Rivera, B. (Nexo Revista Científica, 2018)
Given the importance of the research component to provide pertinent answers to economic and social problems and demands, decision-making in terms of scientific policy, resource management and infrastructure development in university institutions, it is necessary to evaluate the impact of scientific investigations carried out. Research is a strategy of searching for knowledge, as well as a source of innovation and constant learning of reality, becoming a key factor for technological and educational transformation. The purpose of this review article is to perform an analysis of the different methodologies and indicators academic, economic, social and technological that have been implemented to evaluate the impact of university research. Given the importance of the research component to provide pertinent answers to economic and social problems and demands, decision-making in terms of scientific policy, resource management and infrastructure development in university institutions, it is necessary to evaluate the impact of scientific investigations carried out. Research is a strategy of searching for knowledge, as well as a source of innovation and constant learning of reality, becoming a key factor for technological and educational transformation. The purpose of this review article is to perform an analysis of the different methodologies and indicators academic, economic, social and technological that have been implemented to evaluate the impact of university research.